Innovative Zakat Management with Blockchain: A Detailed Study of LAZNAS BMH’s Pioneering Role - Eko Muliansyah (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study explores the transformative impact of blockchain technology on zakat management, focusing on its implementation by LAZNAS BMH—Indonesia’s pioneering zakat institution to adopt this innovation. Combining quantitative and qualitative methods, the research reveals that blockchain significantly enhances transparency, operational efficiency, and donor trust through immutable records, real-time reporting, and automated distribution via smart contracts. Despite technical challenges and low internal consistency in early survey instruments, findings show a positive perception among donors and beneficiaries, who value traceability, fairness, and speed. Furthermore, qualitative insights emphasize the importance of user education and inclusive design for broader adoption. While a visible gap remains between donations and disbursements, this reflects structured programmatic workflows rather than inefficiency. Ultimately, the study positions blockchain not only as a technical solution, but as a values-driven innovation that redefines trust and accountability in Islamic philanthropy. LAZNAS BMH stands as a compelling model for digital transformation in the nonprofit sector, offering both a technological blueprint and a moral compass for the future of Zakat.